(untitled) (IAHS Medical Journal, 2024)
Background: Smoking seems to be a symbol of adulthood during stress and loneliness to many people. It is well established that most adults start tobacco use in late childhood or adolescence and continue lifelong. This study aimed to determine the smoking pattern among adult populations in a selected community of Bangladesh. Materials and methods: A descriptive cross-sectional study was conducted during May 2022 among adult populations in Raozan Upazila of Chattogram. 120 adults were included in the study by convenience sampling and information were collected by face to face interview. Various statistical analysis were performed. Results: Out of 120 respondents 115(96%) were male, 20(10%) were illiterate, 50(42%) were labor and 60(50%) belonged to lower middle class. Among the total respondents, 93(77%) were married. From the study, it was observed that majority 42(30%) belonged to age between 51-60 years. Out of 120 smokers, almost 90(75%) smoked cigarettes and only 12(10%) used to chew tobacco leaves. Among the smokers, 70(58.3%) used to smoke outside the house while only 6(5%) used any hidden place to smoke. Regarding health related problems, 51(42.5%) had breathing problems and 37(30.8%) had cough. 110(91.67%) used to smoke regularly whereas 10(8.33%) used to smoke ocassionally. Conclusion: In Bangladesh, little is known by the people regarding the harmful effects of smoking and associated risk factors. Special regulations and actions should be implemented to curb current adolescent smoking patterns. IAHS Medical Journal Vol 7(1), June 2024; 40-43